Deteksi Gen Kdr pada Nyamuk Anopheles di Kabupaten Maluku Tenggara Barat - Hanna S.I Kawulur; Hotma Martogi Lorensi Hutapea; Ivon Ayomi; Melda Suebu; Mardi Raharjo Pardi (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2021)
Malaria is still a health problem in Indonesia, particularly in Eastern part of Indonesia. The use of LLIN insecticide bed nets is one of the efforts to reduce the malaria morbidity rate by protecting human from malaria vector bites. The Anopheles flavirostris, Anopheles barbirostris, and Anopheles subpictus mosquitoes are three of the species reported as malaria vectors in West-Southeast Maluku Regency. The aim of this research was to detect the kdr gene in An. flavirostris, An. barbirostris, and An.subpictus mosquitoes collected from Alusi Kelaan village, West-Southeast Maluku Regency. The research was conducted at the Papua Biomedical Research and Development Center, in June 2016. A total of six An. flavirostris, 42 An. barbirostris, and 24 An. subpictus were pooled separately for genomic DNA extraction. The sample used was the An. flavirostris, An. barbirostris, and An. subpictus that survived after the impregnated paper test. The kdr gene detection was carried out using quantitative PCR (qPCR) focused on points V1010 and L1014. The results showed that there were no kdr mutant strains in the An. flavirostris, An. barbirostris, and An. subpictus. These results indicated that the sensitivity of pyrethroid insecticides contained in LLIN mosquito nets to An. flavirostris, An. barbirostris, and An. subpictus mosquitoes was not decreased in West Southeast Maluku Regency.